Influence of Roadway Cross-Section Shape on Gas Explosion Shock Wave Law in U-Type Ventilation Working Faces - Jiajia Liu; Mengqi Shen; Shouqi Chen; Ming Yang (Shock and Vibration)
In U-shaped ventilation working face, different tunnel section shapes are one of the important factors affecting the propagation of gas explosion shock wave. In order to study the propagation law of gas explosion shock wave in working face, the numerical simulation study was carried out by using Fluent simulation software combined with the actual situation of gas explosion in #415 working face of Chenjiashan Coal Mine in Shaanxi Province. By constructing a three-dimensional mathematical and physical model, a simulation study of the upper-corner gas explosion was carried out. The results are described as follows. (1) After the gas explosion shock wave propagates 40 m, the overpressure peak equidistant difference tends to be stable and attenuates and propagates in the form of a single shock wave. The study determines that the effective length of the U-shaped ventilation inlet/return tunnel is 40 m. (2) When the tunnel section is trapezoidal, the initial overpressure of the gas explosion shock wave propagating to the inlet/return airway is the highest, followed by rectangular and semicircular arches, but the internal overpressure attenuation trend of different cross-sectional shapes is the same. (3) The gas explosion shock wave propagates radially along the working face section during the working face propagation. The farther away the location is from the upper corner of the tunnel during a gas explosion with different cross-sectional shapes, the closer the cutoff overpressure peak is. The attenuation trend of overpressure with the propagation distance conforms to the power function law. The research results provide an important theoretical direction for the numerical simulation of gas explosions in coal mining faces.